Enhancing Sociolinguistic Competence through Language Environment: The Role of Visual and Interactive Exposure - wadi, Namlul; Abidin, Munirul; Yurisa, Penny Respati; Farisandi, Farisandi; Maulidi, Ilham (Borneo Journal of Language and Education, 2026)
This study investigates the causal impact of language environment components specifically Visual Exposure Intensity and Interactive Exposure Intensity on the sociolinguistic competence of students at TMI (Tarbiyatul Mu'allimien al-Islamiyah) Al-Amien Prenduan Islamic Boarding School. Utilizing a quantitative Ex-Post Facto design with Path Analysis on 310 respondents, the research deconstructs the "language environment" into visual constructs (linguistic landscape) and interactive constructs (social pressure). The findings reveal a fundamental asymmetry: Visual Exposure Intensity showed no significant effect on sociolinguistic competence (p > 0.05), challenging the assumed efficacy of passive linguistic landscapes. Conversely, Interactive Exposure Intensity emerged as a significant determinant (p < 0.05), confirming that sociolinguistic nuances are acquired through negotiation of meaning and social friction rather than passive observation. However, the low determination coefficient (R² = 9.2%) suggests that unmeasured internal factors (such as motivation and aptitude) play a dominant role alongside environmental factors. The study concludes that effective language environment engineering must prioritize active social interaction over static visual displays.